Correlation between domain wall creep parameters of thin ferromagnetic films - Quinteros, Cynthia Paula (2018)
Designing magnetic materials for potential applications based on domain wall motion requires the knowledge of the relationship between physical properties and phenomenological parameters characterizing domain wall dynamics. We address in this work the study of magnetic-field-driven domain wall motion within the creep regime on a prototypical metallic Pt/Co/Pt stack with perpendicular magnetic anisotropy. By controlling the deposition characteristics, different magnetic properties are achieved, giving rise to different creep parameters. Those phenomenological parameters are found to collapse in a single linear dependence for all samples based on the same material. Moreover, using data in the literature, we show that the same behavior is observed in Au/Co/Au and Tb/Fe based samples. We therefore obtain a pair of global parameters that fully characterize the family of domain wall velocity-field curves within the creep regime for each group of samples, which can be used as input for the optimization of materials.